Taxonomical study on the mollusks collected in Marion-Dufresne (MD55) and other expeditions to SE Brazil: the Fissurellidae (Mollusca, Vetigastropoda) - Simone, Luiz Ricardo L.; Cunha, Carlo M. (Zootaxa, 2014)
The Fissurellidae collected by the Marion-Dufresne Expedition, as well as other regional expeditions to SE Brazil are examined taxonomically, treating 21 species, of which 20 are new. The following new species are described (order according to depth range; species marked with * are from expeditions other than MD55): Cornisepta uirapa (790–940 m), Cornisepta arrepiata (295–1,050 m), Cornisepta aninga (295–1,050 m), Cranopsis hycavis (637 m), Cranopsis nymphalis (295 m), Cranopsis enigmatica (790–940 m), Cranopsis cearensis* (250 m), Cranopsis apostrema (110–940 m), Cranopsis alaris (250–450 m), Cranopsis canopa* (250 m), Cranopsis columbaris* (250 m), Emarginula suspira (54–940 m), Emarginula icosisculpta (10–12 m), Manganesepta atiaia (950–1,570 m), Profundisepta denudata* (3,000 m), Puncturella volcano (607–620 m), Rimula leptarcis (85–105 m), Zeidora pussa (607–940 m), Zeidora crepidula (790–940 m), Hemimarginula hemitoma (1–105 m). Diodora mirifica Métivier, 1972 (10–12 m), common in Brazilian oceanic islands, is the only fissurellid species previously known from that area. The genera Cornisepta, Cranopsis, Manganesepta, Profundisepta, Zeidora, and Hemimarginula are reported for the first time from Brazil. Emarginula suspira is named for material that has been misidentified as E. tuberculosa, a Miocene Mediterranean fossil